Trifekta Motivasi Kerja: Budaya Industri, Program Magang Guru Produktif, dan Komunitas Belajar dalam Konteks Pendidikan Vokasi - Waryanto, Waryanto; Maryanto, Maryanto; Egar, Ngasbun (Media Manajemen Pendidikan, 2025)
The research was designed to analyze the influence of industrial culture, productive teacher internship programs, and learning communities on the work motivation of vocational high school (Sekolah Menengah Kejuruan, SMK) teachers across Kendal Regency, both partially and simultaneously. Employing a quantitative approach with an explanatory research design, the study encompassed all public and private vocational high schools in Kendal Regency, Central Java Province, totaling 29 institutions. The population of this research comprised 315 productive teachers. A sample of 176 teachers was determined through the application of the Slovin formula. Proportional sampling was the technique utilized for sample selection. Data collection was conducted via questionnaires. The data were analyzed using multiple linear regression analysis techniques. The research findings indicate that, on an individual basis, as verified by the t-statistic values with a significance level of p<0.05, industrial culture, productive teacher internship programs, and learning communities exert a positive and significant influence on work motivation. Furthermore, the research findings demonstrate that these three variables simultaneously affect work motivation, with a coefficient of determination (R2) of 0.584. The most substantial contribution to work motivation in the simultaneous model originates from the productive teacher internship program as indicated by the value of β=0.433, p<0.001).